Penguatan Agribisnis Melon Wates Blitar melalui IoT, Diversifikasi Produk, dan Digital Branding - Nilawati Fiernaningsih; R. Moechammad Sarosa; R N Akhsanu Takwim; Anna Widayani; Pudji Herijanto (Jurnal Medika: Medika, 2025)
This community service program was carried out to address the main problems faced by the partner groups, namely the low production efficiency among melon farmers and the limited processing capacity of melon-based products in downstream partners. The purpose of this activity was to improve the productivity and quality of melon cultivation through the implementation of an Internet of Things (IoT) control system in the greenhouse, as well as to enhance the production capacity of processed melon chips using an upgraded vacuum fryer with a larger capacity. The applied methods included production system optimization, technology implementation assistance, training in production information management, and digital branding reinforcement. The results showed significant improvements in efficiency and product quality in two IoT-based automated greenhouses. Meanwhile, the downstream partner successfully increased melon chip production capacity from 10 kg to 30 kg per process, with improved product consistency and shelf life. Furthermore, the digital branding strategy positively influenced market competitiveness and consumer trust in the partners’ products